THE INTERNATIONAL RESPONSE TO THE CHECHEN WARS - COLEAŞĂ, Maria-Cristina (Studia Universitatis Babes-Bolyai Studia Europaea, 2017)
The aim of this essay is to assess the impact of the Chechen Wars on the international community and to analyze the motives behind the modest international response to the issue. While the first section of the paper provides an overview of the conflicts, their background and their nature, the second section analyzes the international context in which the wars occurred and attempts to offer scholarly results to the following questions: What caused the indifferent international reaction to the Chechen Wars? What was different in these wars that prompted the neglect of the Western policy makers?